The effects of gastrin, gastric inhibitory polypeptide, secretin, and the octapeptide of cholecystokinin upon immunoreactive somatostatin release by the perfused canine pancreas. - Ipp, E (1977)
The effects of gastrin, gastric inhibitory polypeptide, secretin, and the octapeptide of pancreozymin-cholecystokinin on immunoreactive somatostatin release were studied in the isolated perfused dog pancreas. Gastrin at a concentration of 65 ng/ml and the octapeptide of pancreozymin-cholecystokinin at a concentration of 25 ng/ml produced a prompt, but transient statistically significant, twofold rise in mean somatostatin concentration. Secretion at a concentration of 0.3 U/ml and gastric inhibitory polypeptide concentration of 58 ng/ml produced a prompt two- to threefold rise in mean somatostatin release, which persisted throughout the perfusion period. With all four polypeptides the pattern of the somatostatin response resembled that of insulin. It appears that pancreatic somatostatin release is stimulated by gastrointestinal hormones that influence the secretion of insulin and glucagon.